Prioritising abstract test cases: an empirical study - Huang, Rubing; Zong, Weiwen; Chen, Tsong Yueh; Towey, Dave; Zhou, Yunan; Chen, Jinfu (Institution of Engineering and Technology, 2019)
Test-case prioritisation (TCP) attempts to schedule the order of test-case execution such that faults can be detected as quickly as possible. TCP has been widely applied in many testing scenarios such as regression testing and fault localisation. Abstract test cases (ATCs) are derived from models of the system under test and have been applied to many testing environments such as model-based testing and combinatorial interaction testing. Although various empirical and analytical comparisons for some ATC prioritisation (ATCP) techniques have been conducted, to the best of the authors' knowledge, no comparative study focusing on the most current techniques has yet been reported. In this study, they investigated 18 ATCP techniques, categorised into four classes. They conducted a comprehensive empirical study to compare 16 of the 18 ATCP techniques in terms of their testing effectiveness and efficiency. They found that different ATCP techniques could be cost-effective in different testing scenarios, allowing us to present recommendations and guidelines for which techniques to use under what conditions. © The Institution of Engineering and Technology 2018.